Chromosome analysis in Pseudopaludicola (Anura, Leiuperidae), with description of sex chromosomes XX/XY in P-saltica - Duarte, Thiago C.; Veiga-Menoncello, Ana Cristina P.; Lima, Janaina F. R.; Strussmann, Christine; Del-Grande, Maria L.; Giaretta, Ariovaldo A.; Pereira, Emiliane G.; Rossa-Feres, Denise C. [UNESP]; Recco-Pimentel, Shirlei M. (Wiley-Blackwell, 2010)
Taxonomic changes have frequently occurred in the anuran genus Pseudopaludicola as a consequence of high morphological similarity among its species. The present work reports karyotypic analysis of three Pseudopaludicola species sampled in their type locality and four Pseudopaludicola populations from distinct localities, aiming at contributing to the systematics of this genus. Chromosomes were stained with Giemsa or submitted to the silver staining (Ag-NOR) and C-banding techniques. The karyotype was 2n=22 in P. mineira, Pseudopaludicola sp. and two populations of P. saltica. The chromosome pair 8 was heteromorphic in P. saltica, characterizing a XX/XY sex-determination system with telocentric X and submetacentric Y. Highly similar karyotypes with 2n=18 chromosomes were observed in P. canga, P. aff. canga from Barreirinhas, State of Maranhao, Uberlandia, State of Minas Gerais and Icem, State São Paulo. The high similarity among the karyotypes 2n=18 suggested that the populations of P. aff. canga belong to the group 'pusilla', the same group of P. canga. The data demonstrated also that P. aff. canga from Barreirinhas (northeast region) is cytogenetically identical to P. canga with regarding the NOR site position in pair 3 and the presence of a heterochromatic block in the pair 2, whereas P. aff. canga from Uberlandia and Icem (southeast) had the NOR in the pair 9. Moreover, the cytogenetic data discriminated P. mineira and Pseudopaludicola sp. from the previously analyzed species with 22 chromosomes, and suggested that Pseudopaludicola sp. is an undescribed species. Sexual heteromorphic chromosomes are firstly reported in Pseudopaludicola and the data indicated the need of an extensive taxonomic review in this genus.